Childhood measles contributes to post‐bronchodilator airflow obstruction in middle‐aged adults: A cohort study. Issue 8 (20th March 2018) - Perret, Jennifer L.; Matheson, Melanie C.; Gurrin, Lyle C.; Johns, David P.; Burgess, John A.; Thompson, Bruce R.; Lowe, Adrian J.; Markos, James; Morrison, Stephen S.; McDonald, Christine F.; Wood‐Baker, Richard; Svanes, Cecilie; et al.
Abstract: Background and objective: Chronic obstructive pulmonary disease (COPD) has potential origins in childhood but an association between childhood measles and post‐bronchodilator (BD) airflow obstruction (AO) has not yet been shown. We investigated whether childhood measles contributed to post‐BD AO through interactions with asthma and/or smoking in a non‐immunized middle‐aged population. Methods: The population‐based Tasmanian Longitudinal Health Study (TAHS) cohort born in 1961 ( n = 8583) underwent spirometry in 1968 before immunization was introduced. A history of childhood measles infection was obtained from school medical records. During the fifth decade follow‐up ( n = 5729 responses), a subgroup underwent further lung function measurements ( n = 1389). Relevant main associations and interactions by asthma and/or smoking on post‐BD forced expiratory volume in 1 s/forced vital capacity (FEV1 /FVC; continuous variable) and AO (FEV1 /FVC < lower limit of normal) were estimated by multiple regression. Results: Sixty‐nine percent ( n = 950) had a history of childhood measles. Childhood measles augmented the combined adverse effect of current clinical asthma and smoking at least 10 pack‐years on post‐BD FEV1 /FVC ratio in middle age (z‐score: −0.70 (95% CI: −1.1 to −0.3) vs −1.36 (−1.6 to −1.1), three‐way interaction: P = 0.009), especially for those with childhood‐onset asthma. For never‐ and ever‐smokers of <10 pack‐years who had current asthma symptoms, compared with those without childhood measles, paradoxically, the odds for post‐BD AO was not significant in the presence of childhood measles (OR: 12.0 (95% CI: 3.4–42) vs 2.17 (0.9–5.3)). Conclusion: Childhood measles infection appears to compound the associations between smoking, current asthma and post‐BD AO. Differences between asthma subgroups provide further insight into the complex aetiology of obstructive lung diseases for middle‐aged adults. Abstract : Childhood measles infection as a potential early‐life respiratory insult is not linked to chronic obstructive pulmonary disease (COPD) in adult life by itself. However, this prospective study found childhood measles increased the risk of post‐bronchodilator airflow obstruction for middle‐aged adults through its interaction with the combined effects of current adult asthma and smoking. See related Editorial